Reformas no neoliberalismo e protestos sociais nos governos petistas (2003-2016) - Santos, Thais Cristina Lima Dos [UNIFESP] (2020)
Our research sought to verify why the numerical protagonism of popular classes and movements did not become political protagonism after June 2013, when there was a political crisis in the government of Dilma Rousseff, as well as within the classes and fractions of classes that supported them the “petistas” governments since 2003. The class struggle is at the basis of the president's impeachment, as it was the result of the restorative offensive of orthodox neoliberalism, led by the bourgeois fractions, dissatisfied with the conduct of the mitigated neoliberalism practiced by “petistas” governments. The economic and social policy carried out by these governments favored the conditions of struggle for the working class and for social movements, which achieved improvements and the expansion of their rights. However, the favorable conjuncture in the reivindication for these subjects, did not culminate in popular autonomy in relation to “petistas” governments, easing social protests, in the sense that there was no search for structural reforms, nor a direct confrontation with these governments and their actions. The favorable conjuncture also interfered in the capacity and willingness to unify the struggles and popular subjects, fragmenting them, and demonstrating that the divergences and the deficiency in the dialogue within the popular classes and movements, were accentuated in the “petistas” governments. However, these difficulties must not be understood only as a result of the actions of the governments of Lula and Dilma Rousseff, but, above all, they are consequences of neoliberalism itself. Finally, we consider that a set of factors that occurred in the period from 2003 to 2016, provide an explanation for the non-conversion of the numerical protagonism of these subjects into political protagonism after 2013.